Cash Budgeting and Organizational Performance of Private Firms in Uganda: A Case of Kabale District, Western Uganda - Eton, Marus; Fabian, Mwosi; Benard, Patrick Ogwel (International Journal of Management and Commerce Innovations, 2018)
Cash budgeting should ensure that organizational expenditures match planned cash flows. The study sought to examine the role of Cash budgeting in improving organizational performance of private business firms in Uganda. The study adopted a correlation, descriptive and analytical design, with both quantitative and qualitative approaches being used. Data was collected by use of questionnaires which was self administered. A sample of 115 was chosen, the findings indicated the correlation between cashing budgeting and organizational performance (r = .638) which showed a strong association between the two variables. In addition (Adjusted R Square = .402) indicated that cash budget in the institutions investigated influences about 40.2% of the entire organizational performance. The findings also indicate that cash budgeting stabilizes profitability levels, ensures that organizational expenditures are kept in line with planned cash flows, which also enhances the capacity to predict the likelihood of excess cash. The study recommended that business organizations should focus on profitability levels more than struggling to meet their financial obligations. Performing organizations should establish sound liquidity management practices and should endeavor to employ strategic plans in realizing organizational objectives.